The Role of Business Incubators in Enhancing Human Resource Competence and Encouraging Entrepreneurship among Young People - Sutrisno; Mustafa, Fahrina; Suparwata, Dewa Oka (PT. LITERASI SAINS NUSANTARA, 2024)
Quality human resources (HR) are one of the main pillars in the economic development of a country. The unemployment rate among young people remains relatively high in many areas. Lack of access to training and adequate resources often serves as a major barrier for youth to start their own businesses. Intervention is needed to boost entrepreneurship among young people. This research aims to examine the role of business incubators in enhancing HR competence and promoting entrepreneurship among young people in general. This study is a literature review with a qualitative approach. Data were collected from scholarly articles published during the period 2005-2024, primarily from Google Scholar, which is a credible platform for academic literature search. The study results indicate that business incubators play a central role in developing and accelerating the growth and success of startup companies in Indonesia, especially among young people. In this context, business incubators not only enhance human resource competence through training programs and mentoring but also encourage entrepreneurship by creating a conducive environment for the development of innovative ideas. Business incubators also serve as a link between various elements in the entrepreneurship ecosystem and have a positive impact on the local economy and society as a whole.